NEBULA101: an open dataset for the study of language aptitude in behaviour, brain structure and function - Alessandra Rampinini; Irene Balboni; Olga Kepinska; Raphael Berthele; Narly Golestani (Scientific Data)
Abstract This paper introduces the “NEBULA101 - Neuro-behavioural Understanding of Language Aptitude” dataset, which comprises behavioural and brain imaging data from 101 healthy adults to examine individual differences in language and cognition. Human language, a multifaceted behaviour, varies significantly among individuals, at different processing levels. Recent advances in cognitive science have embraced an integrated approach, combining behavioural and brain studies to explore these differences comprehensively. The NEBULA101 dataset offers brain structural, diffusion-weighted, task-based and resting-state MRI data, alongside extensive linguistic and non-linguistic behavioural measures to explore the complex interaction of language and cognition in a highly multilingual sample. By sharing this multimodal dataset, we hope to promote research on the neuroscience of language, cognition and multilingualism, enabling the field to deepen its understanding of the multivariate panorama of individual differences and ultimately contributing to open science.